XRCC1-mediated repair of strand breaks independent of PNKP binding - Horton, Julie K. (DNA Repair (Amst), 2017)
Repair of DNA-protein crosslinks and oxidatively damaged DNA base lesions generates intermediates with nicks or gaps with abnormal and blocked 3′-phosphate and 5′-OH ends that prevent the activity of DNA polymerases and ligases. End cleaning in mammalian cells by Tdp1 and PNKP produces the conventional 3′-OH and 5′-phosphate DNA ends suitable for completion of repair. This repair function of PNKP is facilitated by its binding to the scaffold protein XRCC1, and phosphorylation of XRCC1 by CK2 at several consensus sites enables PNKP binding and recruitment to DNA damage. To evaluate this documented repair process, a phosphorylation mutant of XRCC1, designed to eliminate PNKP binding, was stably expressed in Xrcc1(−/−) mouse fibroblast cells. Analysis of PNKP-GFP accumulation at micro-irradiation induced damage confirmed that the XRCC1 phosphorylation mutant failed to support efficient PNKP recruitment, whereas there was rapid recruitment in cells expressing wild-type XRCC1. Recruitment of additional fluorescently-tagged repair factors PARP-1-YFP, GFF-XRCC1, PNKP-GFP and Tdp1-GFP to micro-irradiation induced damage was assessed in wild-type XRCC1-expressing cells. PARP-1-YFP recruitment was best fit to two exponentials, whereas kinetics for the other proteins were fit to a single exponential. The similar half-times of recruitment suggest that XRCC1 may be recruited with other proteins possibly as a pre-formed complex. Xrcc1(−/−) cells are hypersensitive to the DNA-protein cross-link inducing agent camptothecin (CPT) and the DNA oxidative agent H(2)O(2) due in part to compromised PNKP-mediated repair. However, cells expressing the PNKP interaction mutant of XRCC1 demonstrated marked reversal of CPT hypersensitivity. This reversal represents XRCC1-dependent repair in the absence of the phosphorylation-dependent PNKP recruitment and suggests either an XRCC1-independent mechanism of PNKP recruitment or a functional back-up pathway for cleaning of blocked DNA ends.